Variação e multidimensionalidade no uso do espaço em muriquis-do-norte (Brachyteles hypoxanthus). - Lima, Marlon (2022)
Studies carried out over almost 40 years in the population of northern muriquis (Brachyteles hypoxanthus) in the Private Natural Heritage Reserve Feliciano Miguel Abdala, in Minas Gerais, Brazil, offer a great opportunity to assess the